LINGUISTIC INTERPRETATIONS OF TEXT BASED ON SYSTEMIC CODING - Liliek Soepriatmadji (Universitas Stikubank (UNISBANK) Semarang, 2014)
This article is a short and simple discussion of how someone should use Systemic Coder in order to linguistically analyze a text. Understanding of certain linguistic theories is a must for those who may conduct a linguistic analysis with this product of computational linguistics. They must decide the unit of analysis, design the scheme, do the coding, and provide the interpretation, which are all based on linguistic theories. Explanation of how Systemic Coder is applied in order to help interprete a text and the SFG-based interpretation of text is provided in the discussion. Key words: Systemic Coder, linguistic interpretation, computational linguistics, SFG